The rhetoric function of polarity in one of Ephrem the Syrian's hymns on the church - Botha, P. J. (Journal for semitics, 1991)
St. Ephrem was the most prominent church father of a true Semitic Christianity. He lived in the fourth century and was a prolific writer who composed theological hymns for liturgical use. In a Semitic vein, his poetry is characterised by the use of poetic stratagems such as imagery and polarity. The incidence and rhetoric function of polar structures in his hymns merit investigation. In this paper, the first hymn in Ephrem's cycle on the Church is analysed with regard to the construction and function of polarities. The conclusion is reached that polar structures serve to establish paradoxes which Ephrem uses as a powerful aid in his efforts to warn against the dangers of ecclesiastical disunity and covetousness.